PENGARUH PUPUK SP-36 DAN FUNGI MIKORIZA ARBUSCULA TERHADAP SERAPAN FOSFAT TANAMAN JAGUNG (Zea Mays L.) PADA OXIC DISTRUDEPTS LEMBAN TONGOA - Pamuna, Katrin; Darman, Saiful; Pata'dungan, Yosep Soge (AGROTEKBIS, 2013)
Incepticol is known as low fertile soil as well Oxic Dystrudepts which is a sub group. The objective of this study was to investigate the effect of P (Phosphor) fertilizer and mychorriza arbuscular on the availability concentration of P soil and uptake by maize (Zea mays L.) on Oxic Dystrudepts soil of Lemban Tongoa area. Randomized block design (RBD) in factorial was used as research design. The first factor was P fertilizer (source SP-36), treated in seven different concentrations namely 0, 50, 100, 150, 200, 250, and 300 kg P ha-1, and with and without mycorrhizal fungi application as second factor. Each treatment was repeated three times. The results showed that all doses of the SP-36 fertilizer increase significantly the availability concentration of P in soil, and the present of arbuscular mycorrhizal fungi significantly increase P uptake by maize. The higher the doses of fertilizer SP-36 the higher the P-total and P uptake find in maize, and sharper increase when treated with mycorrhizae.